Diosmetin, Methylated Flavonoid Mitigates Ovalbumin Induced Allergic Rhinitis in Mice by Attenuating Inflammatory Signaling Proteins - Yu, Jia; Xu, Yuanyuan (Indian Journal of Pharmaceutical Education and Research, 2024)
Background: Allergic Rhinitis (AR) is a chronic disorder that affects about 15-20% of the global population. In severe cases, AR causes sleep deprivation and impairs work performance and quality of life. Untreated allergic rhinitis may also lead to asthma. Intranasal corticosteroids and oral antihistamines are the most commonly prescribed drugs for allergic rhinitis. The long term intake of these drugs causes various side effects; hence, an alternative drug is required to treat allergic rhinitis. Flavonoids are ubiquitous phytochemicals present in most plants and have been proven to have immense pharmacological properties. Objectives: In this study we assessed the ameliorating effect of one such flavonoid diosmetin against AR in mice. Materials and Methods: BalB/c mice were induced AR with Ovalbumin (OVA) and treated with 10, 20 mg/kg of diosmetin. Nasal symptoms in mice were assessed and then subjected to nasal lavage collection. The levels of OVA specific IgE antibody and histamine were quantified in the experimental animals. Allergic markers Prostaglandin-D2 (PGD2), Leukotriene C4 (LTC4) and Eosinophil Cationic Protein (ECP) were measured in the Nasal Lavage Fluid (NALF) of the animals. Pro-inflammatory cytokines interleukin and TNF-α were quantified in both the NALF and nasal tissue sample of the experimental animals. Eosinophilic counts in the nasal tissue were done to confirm the rhinitis induction. To assess the antioxidant property of diosmetin the levels of oxidative and antioxidant levels were quantified in the nasal mucosal tissue. Results: Diosmetin treatment significantly inhibited the rhinitis nasal symptoms it decreased the levels of OVA specific IgE antibody and histamine in AR induced mice. It significantly attenuated the synthesis of allergic markers thereby inhibited the allergic induction which was evidenced with eosinophilic count results. Diosmetin treatment significantly mitigated the synthesis of pro-inflammatory cytokines which observed in both NALF and nasal mucosa tissue. All together our result proves diosmetin scavenged free radicals and rendered anti-inflammatory thereby prevented mice from OVA induced allergic rhinitis. Conclusion: Diosmetin may be a potent drug to treat allergic rhinitis since it targets multiple signaling pathways to ameliorate allergic rhinitis. Further studies may confirm the usage of diosmetin as reliable drug for allergic rhinitis.
Keywords: Allergic reaction; Ovalbumin; Inflammatory cytokines; Diosmetin; Leukotriene C4